2019
DOI: 10.1021/acsami.9b09851
|View full text |Cite
|
Sign up to set email alerts
|

Scaled-up Direct-Current Generation in MoS2 Multilayer-Based Moving Heterojunctions

Abstract: Techniques for scaling-up the direct-current (dc) triboelectricity generation in MoS 2 multilayer-based Schottky nanocontacts are vital for exploiting the nanoscale phenomenon for real-world applications of energy harvesting and sensing. Here, we show that scaling-up the dc output can be realized by using various MoS 2 multilayer-based heterojunctions including metal/semiconductor (MS), metal/insulator (tens of nanometers)/semiconductor (MIS), and semiconductor/insulator (a few nanometers)/semiconductor (SIS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 33 publications
1
58
0
1
Order By: Relevance
“…The metal-semiconductor-based DC-TENG with low impedance of 620 Ω can produce an average open-circuit voltage of 20 mV and short-circuit current of 20 µA. Moreover, Liu et al [104] demonstrated DC output through various MoS 2 -based moving heterojunction including MS (metal-semiconductor), MIS (metal-insulator-semiconductor), and SIS (semiconductorinsulator-semiconductor), as shown in Figure 5e,f. In the MS contact, the output voltage and current up to 0.3 V and 0.6 µA will be produced, when MoS 2 rotates circularly on the Al substrate.…”
Section: Development Of Semiconductor-based Dc-tengs In Bulk Contactmentioning
confidence: 99%
See 2 more Smart Citations
“…The metal-semiconductor-based DC-TENG with low impedance of 620 Ω can produce an average open-circuit voltage of 20 mV and short-circuit current of 20 µA. Moreover, Liu et al [104] demonstrated DC output through various MoS 2 -based moving heterojunction including MS (metal-semiconductor), MIS (metal-insulator-semiconductor), and SIS (semiconductorinsulator-semiconductor), as shown in Figure 5e,f. In the MS contact, the output voltage and current up to 0.3 V and 0.6 µA will be produced, when MoS 2 rotates circularly on the Al substrate.…”
Section: Development Of Semiconductor-based Dc-tengs In Bulk Contactmentioning
confidence: 99%
“…[105] By sliding a carbon aerogel on a p-type Si wafer with a thin SiO 2 layer, a direct current of 15 µA and voltage of 2 V is obtained, which is much higher than other semiconductor-based DC system and sufficient for the practical applications. [90,101,104] Moreover, introducing transparent materials such as indium tin oxide (ITO), the performance of semiconductor-based DC system can be enhanced by coupling electric fields induced with irradiation and friction (Figure 5h). A prototype was developed using ITO glass as slider and Si wafer as the substrate to prove the feasibility.…”
Section: Development Of Semiconductor-based Dc-tengs In Bulk Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional TENGs usually use organic polymer insulation materials, and the charges generated by friction tends to accumulate on the surface of the material, resulting in an alternating output . Recently, semiconductor materials began to attract researchers' interest, and a series of work has made great progress: the tribotunneling nanogenerator based on sliding metal–insulator–semiconductor (MIS) structure, the moving Schottky diode based on metal–semiconductor (MS) structure, the triboelectric cell based on PN junction structure, and other moving heterojunction nanogenerator . Thundat and Liu et al realized an ultrahigh current density MIS nanogenerator due to quantum mechanical tunneling of the ultrathin natural oxide layer .…”
Section: Introductionmentioning
confidence: 99%
“…sliding metal-insulator-semiconductor (MIS) structure, [14][15][16][17] the moving Schottky diode based on metal-semiconductor (MS) structure, [18][19][20] the triboelectric cell based on PN junction structure, [21][22][23] and other moving heterojunction nanogenerator. [24] Thundat and Liu et al realized an ultrahigh current density MIS nanogenerator due to quantum mechanical tunneling of the ultrathin natural oxide layer. [14][15][16] Lin et al designed a moving Schottky diode generator with high current density output which is based on the built-in electric field separation.…”
mentioning
confidence: 99%